1954
DOI: 10.1172/jci103020
|View full text |Cite
|
Sign up to set email alerts
|

Surface as a Quantitative Factor in Prothrombin Utilization1

Abstract: The accelerating effect of foreign surfaces on coagulation of whole blood has been recognized for many years. In 1863, Lister (1) was aware of the great influence exerted upon the blood by exposure for a very short time to a foreign solid . . . ," and concluded, "The real cause of the coagulation of the blood, when shed from the body, is the influence exerted upon it by ordinary matter. . . ." Since the original observations of Lister, many subsequent investigators have studied this phenomenon (2-15).In the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1956
1956
1971
1971

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The observations that the residual high level of serum prothrombin remaining after clotting of PF plasma was decreased when the plasma was treated with glass before recalcification are in agreement with those of Dick, Jackson, and Conley (8). However, as in the present experiments (Table VII) it was shown that after contact with a large area of glass prothrombin may be partly removed from plasma, we hesitate to attribute the decrease in serum prothrombin after contact with glass, to enhanced prothrombin utilization.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The observations that the residual high level of serum prothrombin remaining after clotting of PF plasma was decreased when the plasma was treated with glass before recalcification are in agreement with those of Dick, Jackson, and Conley (8). However, as in the present experiments (Table VII) it was shown that after contact with a large area of glass prothrombin may be partly removed from plasma, we hesitate to attribute the decrease in serum prothrombin after contact with glass, to enhanced prothrombin utilization.…”
Section: Discussionsupporting
confidence: 89%
“…Conley and his associates (5)(6)(7)(8) have reported that contact with glass markedly shortens the clotting time of silicone prepared "platelet free" plasma and increases its prothrombin utilization. They concluded that glass activates "plasma thromboplastin," a constituent residing in the globulin fraction.…”
mentioning
confidence: 99%
“…When thrombocytopenic blood coagulates, relatively large amounts of prothrombin persist (26,27). Significant amounts may remain in the serum of normal blood, depending upon the manner in which the blood is handled (14). If serum containing prothrombin is mixed with thromboplastic materials or with platelets, additional thrombin is generated (28).…”
Section: Resultsmentioning
confidence: 99%
“…Residual prothrombin in serum was estimated by the method of Quick and Favre-Gilly (13) as modified by Dick, Jackson, and Conley (14). Platelets were counted by the method of Brecher and Cronkite (15).…”
Section: Methodsmentioning
confidence: 99%
“…Cases [7][8][9][10][11][12][13][14][15] Effects of multiple preoperative phlebotomies in nine other cases are summarized in TABLE 2. Three of these patients ( # 10, #13, and Single Phlebotomy Ten patients were subjected to a single phlebotomy prior to surgery.…”
Section: Multiple Phlebotomiesmentioning
confidence: 99%